Handbook of research on smart farming technologies for sustainable agricultural development - Poonia, Ramesh C., 1979- (Engineering Science Reference (an imprint of IGI Global), 2018)
"This book discusses the recent advancement in farming in terms of informatics and communication. It also explores how to improve productivity by introducing sensors, automated machines, smart phones; yield meters and drones"--Provided by publisher.